2007
DOI: 10.1029/2007gl030157
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and the changing hydroclimatology of the Amazon

Abstract: [1] Using a spatially-explicit model, we have projected potential Amazon landscapes based on two possible development scenarios and total forest removal to represent uncertainty in future land cover. We conducted Monte Carlo simulations with a regional climate model driven by these landscapes and by different years to include atmospheric uncertainty. Absent restraints on development, we find that certain areas can expect annual rainfall declines of 3 -5% that persist in spite of introduced uncertainty. These d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…4D) that is larger than the increase in the Temperate case and comparable to the Boreal case. This decrease is also consistent with several Amazon deforestation studies (17,35,36) that showed reduced annual mean rainfall. We conclude from Fig.…”
Section: Significancesupporting
confidence: 76%
“…4D) that is larger than the increase in the Temperate case and comparable to the Boreal case. This decrease is also consistent with several Amazon deforestation studies (17,35,36) that showed reduced annual mean rainfall. We conclude from Fig.…”
Section: Significancesupporting
confidence: 76%
“…Recent studies have investigated the hydrological cycle at the ARB, confirming the occurrence of several extreme hydrological events like droughts, floods, and a marked terrestrial water storage variability during the last years [1][2][3][4][5]. Future scenarios of a complete deforestation in the region point to a restrained water cycle [6,7]. Moore et al [6] suggest that total deforestation of the Amazon would result in a 10-20% decrease in annual rainfall across the entire Amazon basin.…”
Section: Introductionmentioning
confidence: 99%
“…Future scenarios of a complete deforestation in the region point to a restrained water cycle [6,7]. Moore et al [6] suggest that total deforestation of the Amazon would result in a 10-20% decrease in annual rainfall across the entire Amazon basin. The acceleration of human-driven climate change poses serious questions and challenges for conservation strategies at the ARB [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al 2007; Ramos da Silva et al 2008;Walker et al 2009). Their higher resolution presents several advantages.…”
Section: Introductionmentioning
confidence: 99%